Oral health knowledge and its correlation to caries experience among students - Zaharani, Cut Asy Syifa; Molek, Molek; Wijaya, Cindy Denhara; Florenly, Florenly; Susanto, Chandra; Tarigan, Susiani; Putra, Kriswandy; Karen, Yulia (Buletin Kedokteran & Kesehatan Prima, 2025)
Dental caries remains a significant global public health issue, particularly among school-aged children. A lack of knowledge regarding oral health maintenance is considered a primary contributing factor to the high prevalence and severity of caries in this demographic. This study aimed to analyze the influence of oral health maintenance knowledge on the severity of dental caries in Grade 6 students at SDN No. 060833. An analytical observational study with a cross-sectional design was conducted. A total of 39 students were selected using simple random sampling. Data on knowledge were collected using a validated questionnaire, while caries severity was assessed through direct oral examination and categorized as pit fissure caries, superficial caries, medium caries, or profound caries. Data analysis employed univariate and bivariate methods using the Chi-Square test. The majority of students (64.1%) had poor knowledge of oral health maintenance. The most common caries severity was superficial caries (35.9%), followed by medium caries (30.8%). Bivariate analysis revealed a statistically significant relationship between knowledge level and caries severity (p-value = 0.000). Students with poor knowledge were more likely to experience medium and profound caries. There is a significant influence of the level of knowledge about oral health maintenance on the severity of dental caries in Grade 6 students. Efforts to improve oral health knowledge through targeted education programs in schools are essential to prevent and reduce the severity of dental caries.